2011
DOI: 10.1111/j.1423-0410.2011.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Prednisolone intravenously or Dexamethason orally in random donors reveals equal results in granulocyte collection: a single centre experience

Abstract: Since cytokine--mobilization for granulocyte collections in random donors--is not licensed in Austria, we investigated in a prospective analysis the effects of prednisolone or dexamethasone (DXM) in 153 donors (35 women/118 men) and in the collected products. Either prednisolone (50 mg) intravenously 4 h before granulocyte collection or DXM (8 mg) orally 12 h before collection was given. Collections were performed with the Cobe Spectra (CardianBCT, Lakewood). We recorded a significantly higher percentage of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
1
Order By: Relevance
“…Most of our recipients are pediatric patients with a low body weight. Thus, volume reduction is necessary to avoid a transfusion overload in these patients . At our institution a product volume exceeding 500 mL must be divided into two parts before further processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of our recipients are pediatric patients with a low body weight. Thus, volume reduction is necessary to avoid a transfusion overload in these patients . At our institution a product volume exceeding 500 mL must be divided into two parts before further processing.…”
Section: Discussionmentioning
confidence: 99%
“…In random donors 35 products were collected after mobilization treatment with either prednisolone (P; n = 14) intravenously at a dose of 50 mg 4 hours before collection or alternatively with dexamethasone (DXM; n = 21) at a dose of 8 mg orally 12 hours before the harvest (depending on donor's preference). As published previously with both pretreatments similar amounts of granulocytes (PMNs) can be collected . For random donors a donation frequency of four harvests/year is permitted by the Austrian health authorities as the limiting factor is a dose of P of 200 mg/year and DXM of 32 mg/year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Le choix du corticoïde a aussi fait l'objet d'études. Il n'y a pas de différence entre la stimulation par 8 mg DEXAMETHASONE orale ou par 50 mg de PREDNISONE intra-veineuse (12). Les effets secondaires de la stimulation par corticostéroïdes ont fait l'objet d'une revue (13).…”
Section: Recueil Qualification Biologique Et Distributionunclassified
“…Nevertheless, there are data suggesting less infection‐related mortality after granulocyte transfusions . To obtain enough granulocytes for donation, donors are pretreated with granulocyte colony‐stimulating factor (G‐CSF) and dexamethasone, or with steroids alone for granulocyte mobilization from the bone marrow prior to leukapheresis (from the G‐CSF and dexamethasone‐pretreated donors: ‘GTX’). We have previously shown that these granulocytes function well , although there is a significant partial in vitro Candida killing defect .…”
Section: Introductionmentioning
confidence: 99%